2017
DOI: 10.31229/osf.io/tnmra
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What makes a digital steward: A competency profile based on the National Digital Stewardship Residencies

Abstract: Digital stewardship is the active and long-term management of digital objects towards their preservation for and unencumbered access by future generations. Although the field is rapidly maturing, it still lacks a comprehensive competency profile for practitioners. This is due in part to the relative youth of the field, and to the fact that being an effective steward of digital materials requires highly specialized training that is best acquired through hands-on work. Given the key role that competency profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In their study of projects undertaken in the National Digital Stewardship Residency program (NDSR), Blumenthal et al found that project management skills and technical skills (including metadata, workflow enhancement/development, digital asset management, and digitization) were important. 6 The level of required technical competency tended to vary by project but workflow enhancement stood out as a universally important skill. A 2019 analysis of the latest career trends for information professionals by San Jose State University's (SJSU) iSchool noted that there is increasing demand for project management skills across all career types.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of projects undertaken in the National Digital Stewardship Residency program (NDSR), Blumenthal et al found that project management skills and technical skills (including metadata, workflow enhancement/development, digital asset management, and digitization) were important. 6 The level of required technical competency tended to vary by project but workflow enhancement stood out as a universally important skill. A 2019 analysis of the latest career trends for information professionals by San Jose State University's (SJSU) iSchool noted that there is increasing demand for project management skills across all career types.…”
Section: Introductionmentioning
confidence: 99%